The Utilizing of Three-step Interview in Improving Speaking Ability - Mustari, Sri Hariati (Universitas Malikussaleh, 2019)
This research was conducted to solve students problem in speaking especially the students never practiced to speak each other. The researcher applied the three-step interview technique in improving their speaking ability. The instruments were speaking test, observation sheet and questionnaire. The researcher applied Classroom Action Research. It consisted of two cycles. Each cycle consisted four meetings and four steps. The steps included plan, action, observation, and reflection.The result of the research in the first cycle showed that the students achievement and performance were so low. It could be seen from the students score in the first cycle was 2.74. the highest score in the first cycle was 4 which were acquired by three students but the highest score at the end of the second cycle was 5.3 which was acquired by 4 students. The lowest score in the first cycle was 1.7 which acquired by one student and the lowest score in the second cycle was 3.3 which was acquired by four students. Based on the data, the researcher concluded that three-step interview technique could increase the students ability in speaking. This technique had proven that three-step interview technique was a successful technique to help students in speaking.